THE ROLE OF CLASSROOM ENVIRONMENT IN DRIVING STUDENTS' MOTIVATION TO LEARN ENGLISH - Pelis Petriani; Maulina Maulina; Rahmat Nasrullah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to examine how classroom environment influence students’ motivation and comfort in learning at the Advanced Speaking class. Employing a qualitative approach, data were collected through open-ended questionnaires distributed to 14 participants by a Google Form. The responses were analyzed to identify key environmental factors that contribute to students’ motivation in language learning. The findings reveal that physical elements such as flexible seating arrangements, adequate lighting, proper ventilation, and the use of multimedia tools play a crucial role in creating a supportive and engaging learning atmosphere. Most respondents reported that a well-organized physical environment enhances their focus, participation, and overall comfort during speaking activities. Social interactions within the classroom, including group discussions and peer collaboration, were also found to significantly boost students’ confidence and willingness to speak. Furthermore, emotional support from both teachers and peers contributed to reducing anxiety and fostering a sense of acceptance. These emotional and psychological components were closely linked to an increase in both intrinsic and extrinsic motivation. Overall, the study concludes that a conducive classroom environment encompassing physical layout, social dynamics, and emotional support is essential in motivating students to participate actively in learning advanced speaking course. This current study highlights the need for educators and institutions to consider classroom environment as a strategic factor in designing effective language learning experiences. Future research is recommended to explore more targeted strategies for enhancing students motivation in language classrooms.